THE RESEARCH OF THEORETICAL ASPECTS OF ESTIMATION OF COST OF INNOVATIVELY ACTIVE ENTERPRISE - D. Komonov; L. Mikhailova; A. Sazonov (Вестник университета)
The topical issues of estimation of cost of the enterprise which activity is connected with innovations are considered. The research of merits and demerits of the methods and models necessary for receiving integration assessment in a range of the definition of degree of efficiency of functioning of the enterprise is conducted. It is proved that for increase in economic efficiency of innovative activity of the enterprise on the basis of comprehensive use of the intellectual resources put in the investment potential of the enterprise application of the considered models and methods isn’t enough.